Hereditary and acquired C1-inhibitor-dependent angioedema: from pathophysiology to treatment. (18th May 2016) - Zeerleder, Sacha; Levi, Marcel
Abstract: Uncontrolled generation of bradykinin (BK) due to insufficient levels of protease inhibitors controlling contact phase (CP) activation, increased activity of CP proteins, and/or inadequate degradation of BK into inactive peptides increases vascular permeability via BK-receptor 2 (BKR2) and results in subcutaneous and submucosal edema formation. Hereditary and acquired angioedema due to C1-inhibitor deficiency (C1-INH-HAE and -AAE) are diseases characterized by serious and potentially fatal attacks of subcutaneous and submucosal edemas of upper airways, facial structures, abdomen, and extremities, due to inadequate control of BK generation. A decreased activity of C1-inhibitor is the hallmark of C1-INH-HAE (types 1 and 2) due to a mutation in the C1-inhibitor gene, whereas the deficiency in C1-inhibitor in C1-INH-AAE is the result of autoimmune phenomena. In HAE with normal C1-inhibitor, a significant percentage of patients have an increased activity of factor XIIa due to a FXII mutation (FXII-HAE). Treatment of C1-inhibitor-dependent angioedema focuses on restoring control of BK generation by inhibition of CP proteases by correcting the balance between CP inhibitors and BK breakdown or by inhibition of BK-mediated effects at the BKR2 on endothelial cells. This review will address the pathophysiology, clinical picture, diagnosis and available treatment in C1-inhibitor-dependent angioedema focusing on BK-release and its regulation. Key Messages: Inadequate control of bradykinin formation results in the formation of characteristic subcutaneous and submucosal edemas of the skin, upper airways, facial structures, abdomen and extremities as seen in hereditary and acquired C1-inhibitor-dependent angioedema. Diagnosis of hereditary and acquired C1-inhibitor-dependent angioedema may be troublesome as illustrated by the fact that there is a significant delay in diagnosis; a certain grade of suspicion is therefore crucial for quick diagnosis. Submucosal edema formation in hereditary and acquired C1-inhibitor-dependent angioedema is potentially life threatening and can occur at any age. To date effective therapies for acute and prophylactic treatment are available.